3n-5=-8-10n-6(6+5n)-4

Simple and best practice solution for 3n-5=-8-10n-6(6+5n)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3n-5=-8-10n-6(6+5n)-4 equation:


Simplifying
3n + -5 = -8 + -10n + -6(6 + 5n) + -4

Reorder the terms:
-5 + 3n = -8 + -10n + -6(6 + 5n) + -4
-5 + 3n = -8 + -10n + (6 * -6 + 5n * -6) + -4
-5 + 3n = -8 + -10n + (-36 + -30n) + -4

Reorder the terms:
-5 + 3n = -8 + -36 + -4 + -10n + -30n

Combine like terms: -8 + -36 = -44
-5 + 3n = -44 + -4 + -10n + -30n

Combine like terms: -44 + -4 = -48
-5 + 3n = -48 + -10n + -30n

Combine like terms: -10n + -30n = -40n
-5 + 3n = -48 + -40n

Solving
-5 + 3n = -48 + -40n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '40n' to each side of the equation.
-5 + 3n + 40n = -48 + -40n + 40n

Combine like terms: 3n + 40n = 43n
-5 + 43n = -48 + -40n + 40n

Combine like terms: -40n + 40n = 0
-5 + 43n = -48 + 0
-5 + 43n = -48

Add '5' to each side of the equation.
-5 + 5 + 43n = -48 + 5

Combine like terms: -5 + 5 = 0
0 + 43n = -48 + 5
43n = -48 + 5

Combine like terms: -48 + 5 = -43
43n = -43

Divide each side by '43'.
n = -1

Simplifying
n = -1

See similar equations:

| 2x6x6x6/(4x-4) | | 9n-13=5 | | -32=72 | | 5.37/0.001 | | -13=-16+9k | | 195=(x*16) | | 4(x+7)(x+7)=11 | | 93=4x+7(3x-5)+3 | | 37/8-15/8 | | 9t+7=25 | | [2h-1]=5 | | 9t^1/2-4 | | .5-x/5=-2/5 | | 2.49=0.49+16 | | 11.4=4x-3 | | -3x-39=3x+9 | | 7m=36 | | 3h+18-12=80 | | 380=-18n | | 20x+4y=124 | | 180=2x+(3x+25) | | .75=3/8x-3/2 | | 3(x)=2x+5 | | 3x+3(2x+15)=108 | | 1=2x+.4 | | -8x-5=50 | | 2x+.5=3/5 | | orx^2-10x+25+4x^2-4x+1=29 | | (y/6)-(7/8)=2 | | M/16=64/8 | | 60=6z | | 1600*75= |

Equations solver categories